Chronic Drought Decreases Anabolic and Catabolic BVOC Emissions of Quercus pubescens in a Mediterranean Forest - Saunier, Amélie; Ormeño, Elena; Wortham, Henri; Temime-Roussel, Brice; Lecareux, Caroline; Boissard, Christophe; Fernandez, Catherine (Frontiers in Plant Science, 2017)
Biogenic volatile organic compounds (BVOC) emitted by plants can originate from both anabolism (metabolite production through anabolic processes) and catabolism (metabolite degradation by oxidative reactions). Drought can favour leaf oxidation by increasing the oxidative pressure in plant cells. Thus, under the precipitation decline predicted for the Mediterranean region, it can be expected both strong oxidation of anabolic BVOC within leaves and, as a result, enhanced catabolic BVOC emissions. Using an experimental rain exclusion device in a natural forest, we compared the seasonal course of the emissions of the main anabolic BVOC released by Q. pubescens (isoprene and methanol) and their catabolic products (MACR+MVK+ISOPOOH and formaldehyde, respectively) after 3 years of precipitation restriction (-30% of rain). Thus, we assume that this repetitive amplified drought promoted a chronic drought. BVOC emissions were monitored, on-line, with a PTR-ToF-MS. Amplified drought decreased all BVOC emissions rates in spring and summer by around 40-50 %, especially through stomatal closure, with no effect in autumn. Moreover, ratios between catabolic and anabolic BVOC remained unchanged with amplified drought, suggesting a relative stable oxidative pressure in Q. pubescens under the water stress applied. Moreover, these results suggest a quite good resilience of this species under the most severe climate change scenario in the Mediterranean region.